Faktor yang Mempengaruhi Pemberian Asi Eksklusif: Factors Correlation Exclusive Breastfeeding - Widyawati, Sigit Ambar; Alfan Afandi; Sri Wahyuni (Universitas Ngudi waluyo, 2024)
Exclusive breastfeeding is the provision of breast milk alone to infants up to 6 months without additional fluids or other foods and beverages such as water, formula, orange, honey, tea water, or solid foods such as bananas, papaya, milk porridge, biscuits, rice porridge, and teams. Exclusive breastfeeding for 6 months is recommended by international guidelines based on scientific evidence of the benefits of breast milk for the baby, mother, family, and country. The purpose of this study was to determine the factors that influence exclusive breastfeeding. This research method uses simple random sampling, respondents were selected by random sampling as many as 95 respondents. The results of this study obtained respondents who did exclusive breastfeeding as many as 62 people (65%) and not exclusive breastfeeding as many as 33 people (35%). Based on the results of Chi-Square analysis, it was found that there was a significant relationship between the level of knowledge (p = 0.001), age (p = 0.036), and education level (p = 0.001) with exclusive breastfeeding. Increase knowledge with health promotion and counseling about the benefits and process of exclusive breastfeeding. Abstrak Dalam Bahasa Indonesia ditulis melingkupi 200-500 words. Font Size 11, Times New Roman, spasi Tunggal ASI eksklusif adalah pemberian ASI saja pada bayi sampai 6 bulan tanpa tambahan cairan ataupun makanan lain makanan dan minuman lain yang dimaksud misalnya air putih, susu formula, jeruk, madu, air teh, atapun makanan padat seperti pisang, pepaya, bubur susu, biskuit, bubur nasi, dan tim. Pemberian ASI eksklusif selama 6 bulan dianjurkan oleh pedoman internasional yang didasarkan pada bukti ilmiah tentang manfaat ASI baik bagi bayi, ibu, keluarga, maupun negara. Tujuan dari penelitian ini adalah untuk mengetahui faktor yang mempengaruhi pemberian ASI eksklusif. Metode penelitian ini menggunakan simple random sampling, responden dipilih secara random sampling sebanyak 95 responden. Hasil penelitian ini didapatkan responden yang melakukan pemberian ASI Eksklusif sebanyak 62 orang (65%) dan tidak ASI Eksklusif sebanyak 33 orang (35%). Berdasarkan hasil analisis Chi-Square didapatkan adanya hubungan yang signifikan antara tingkat pengetahuan (p = 0,001), usia (p = 0,036), dan tingkat pendidikan (p = 0,001) dengan pemberian ASI Eksklusif. Meningkatkan pengetahuan dengan promosi kesehatan dan penyuluhan tentang manfaat dan proses pemberian ASI Eksklusif.